A Narrative Review of Toxic Heavy Metal Content of Infant and Toddler Foods and Evaluation of United States Policy - Bair, Emily C. (Frontiers in Nutrition, 2022)
Excessive exposure to inorganic contaminants through ingestion of foods, such as those commonly referred to as ‘heavy metals’ may cause cancer and other non-cancerous adverse effects. Infants and young children are especially vulnerable to these toxic effects due to their immature development and high ‘food intake/ body weight’ ratio. Concerns have been raised by multiple independent studies that heavy metals have been found to be present in many foods in the infant and child food sector. Most recently, reports from the U.S. House of Representatives Subcommittee on Economic and Consumer Policy suggest subpar testing practices, lenient or absent standards, and limited oversight of food manufacturers perpetuate the presence of these contaminants in infant and toddler foods. This article aims to evaluate the current state of policies in the United States and complete a non-biased review of the current body of literature addressing the presence of the so-called heavy metals; arsenic, lead, mercury and cadmium found in infant and toddler foods.